Pengaruh etika Islam terhadap etos kerja penenun songket Palembang / Anisatul Mardiah - Anisatul, Mardiah (2017)
This thesis is to study of the influence of Islamic ethics on the work ethic of Palembang songket weavers. Islamic ethics are values that are arranged for human activity that has been outlined by the revelation of Allah SWT to set human life in order to achieve the best purpose of his existence in this world. Songket weavers selected as the object of study. In this research method used is a mixed methods. As a research method, mixed method focuses on collecting, analyzing and merging the quantitative and qualitative data integration in a single or continuation study. The use of quantitative and qualitative methods in a research provide insights or answers of the research problem better than the use of one of them. The data in this study gained through observation, interviews, questionnaires and documentation. Researchers analyzing qualitative data using descriptive analytical method that is used to explain the concept of Islamic ethics, describing the dynamics of songket weavers, foundation work ethic, and socio-cultural aspects that surround life songket weavers and surrounding communities. Data obtained from the questionnaire is the processed using the SPSS program and analyzed using certain examination. While the scale used in this investigation is based on a Likert Scale. Ethics of Islam is often equated with morals due to the same source, namely the Al-Quran and al-Hadith, good will and purpose also reason and conscience. Islamic ethics are the norms that guide humans to behave well and keep away from bad behavior. While the work ethic of Islam explored and formulated based on the concept of faith and righteous deeds. Without a foundation of faith and righteous deeds, any work ethic can not be Islami. There is no righteous deeds without faith and faith is something that will not work if they do not deliver the righteous deeds. All of which suggests that faith and righteous deeds are series of closely related and even inseparable. The work ethic in Islam is the result of a belief of a moslem that there is relationship between his work and the purpose of his life to obtain the blessing of Allah SWT. The way they understand, appreciate and practice the values of Al-Quran and al-Hadith on the drive to work that shaped the work ethic of Islam. Songket weavers life is no different from people life in general. They also have problems whether family problems, personal or financial problems but it is interesting that they remain focused work as usual as if without the burden of life. They work happily by having jokes or singing even though their work is not easy. They remain work persistently despite having to face problems. They are grateful for the skill they have which is weaving songket. Islamic ethics greatly influenced the work ethic of Palembang songket weavers. Palembang songket weavers work in accordance with Islamic work ethics which are work as worship, professional, diligent, conscientious, disciplined, honest and trustworthy, unyielding (persistent in trying), intends to improve the living standards of families. All the characteristics of the Islamic work ethic certainly make an impact on their work ethics.